EMPLOYER BRANDING PERSEPSIAN TERHADAP KEPERCAYAN PEMIMPIN DAN DAMPAKNYA PADA INTENSI KELUAR: (Studi pada Karyawan Bank di Indonesia) - Marginingsih, Ria; Irawan, Dani (Jurnal Ilmu Keuangan dan Perbankan (JIKA), 2018)
ABSTRACT This study aims to see the influence of employer branding on the exit intention of bank employees in Indonesia which is mediated by trust in leaders. In particular, this study tries to identify how the influence of employer perceived branding on outgoing intentions? Does the employee's trust in the leader affect the intention to leave? How does the influence of employer branding perceptions on outgoing intentions mediated by employee trust in the leader? The population of this study is bank employees who work in groups of state-owned commercial banks, groups of regional government-owned banks, groups of private-owned commercial banks. The sample in this study uses non probability sampling, with the sample is that employees have worked at least one year. For hypothesis testing, this study uses SmartPLS analysis with Likert scale measurement points one (strongly disagree) up to five points (strongly agree). The results of the study of 88 respondents of Bank employees in Indonesia showed that employer branding against intention to leave had a negative and insignificant effect, the influence of employer branding on trust in leaders was positive and significant, the trustworthiness of leaders towards intention was positive and significant, and employer perceived branding towards intention out which is mediated by employee trust in leaders is influential and significant. Keywords: Employer Branding, Intensi Keluar, Kepercayaan pada Pemimpin, Retensi